2010
DOI: 10.1111/j.1365-2982.2010.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of mirtazapine on visceral hypersensitivity in rats with neonatal colon sensitivity

Abstract: Mirtazapine dose-dependently ameliorates visceral hypersensitivity in colonic sensitized rats. Mirtazapine at a high dose improves delayed gastric emptying in colonic sensitized rats but slightly and marginally delays small intestinal transit. Its roles in altering gastrointestinal motility need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
21
2
Order By: Relevance
“…In patients with severe gastroparesis unresponsive to the conventional prokinetic treatment, refractory nausea and vomiting that persisted for over 7 mo were improved dramatically within a few days of once-daily mirtazapine dosing (29). In a previous study, we observed improvement of gastric emptying with mirtazapine in colonic sensitized "IBS-like" rats (42). In the present canine study, we found that mirtazapine improved gastric emptying, gastric accommodation, and colon transit; this was different from what was reported in a clinical study in which mirtazapine showed no effects on gastric emptying in healthy volunteers (7).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In patients with severe gastroparesis unresponsive to the conventional prokinetic treatment, refractory nausea and vomiting that persisted for over 7 mo were improved dramatically within a few days of once-daily mirtazapine dosing (29). In a previous study, we observed improvement of gastric emptying with mirtazapine in colonic sensitized "IBS-like" rats (42). In the present canine study, we found that mirtazapine improved gastric emptying, gastric accommodation, and colon transit; this was different from what was reported in a clinical study in which mirtazapine showed no effects on gastric emptying in healthy volunteers (7).…”
Section: Discussionmentioning
confidence: 96%
“…It is known that many IBS patients display visceral hypersensitivity during colorectal distention (26,30,33). In an earlier study we reported improvement on visceral hypersensitivity with the administration of mirtazapine in colonic sensitized rats (42); however, its effect on the colonic transit was not investigated. In the present study, we found that mirtazapine accelerated colonic transit in normal dogs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, we should pay more attention to FD patients with weight loss and their associated psychological disorders in clinical practice. On the basis of animal studies of antidepressant mirtazapine on the cachexia model and gastrointestinal function [22,23,24], a series of animal and clinical studies (Registration number: ChiCTR-TRC-13003161) are now carrying on to demonstration antidepressant mirtazapine as an effective treatment to manage FD patients with weight loss.…”
Section: Discussionmentioning
confidence: 99%